Reference values for acoustic rhinometry in children from 4 to 13 years old - Straszek, S.; Moeller, A.; Hall, G.; Zhang, Guicheng; Stick, S.; Franklin, P. (2008)
Background: Despite a growing number of studies using acoustic rhinometry (AR) in children, no reference material exists that incorporates the entire age and height interval of preschool children up to puberty for a range of rhinometric variables. The aim of this study is to provide a reference range for nasal volumes and minimum cross-sectional areas (MCAs) in healthy nondecongested children aged 4-13 years old. Methods: Two hundred fifty-six primary school children (mean, 7.95 years; range, 3.8-13.1 years; 123 boys/133 girls) were measured by AR. Variables were MCA (first, second, and absolute minimum) and nasal volumes from 0 to 4 cm (Vol0-4), 0 to 5 cm (Vol0-5), 1 to 4 cm (Vol1-4), and 2 to 5 cm (Vol2-5) into the nasal cavity. Height and weight were measured and atopic status was determined by skin-prick test. Age and current and past respiratory health were recorded from a questionnaire. Results: In multiple linear regression models height was the main predictor for all AR variables although weight also was a significant predictor of MCAs. There was no association between any AR variables with sex, atopy, or hay fever but children with current wheeze (within last 12 months) and asthma had decreased nasal patency. Conclusion: This article presents the most extensive current reference material for AR in nondecongested prepubescent healthy children. The presented reference material will facilitate the interpretation and evaluation of future and present epidemiologic studies based on AR in children. Copyright © 2008, OceanSide Publications, Inc., U.S.A.